O anjo poeta: relação entre literatura e misticismo em escritos de Dom Helder Câmara - Silva, Darci Francisca da (2008)
Interest in spirituality and its literary expressions has become very popular. Being part of this interest, his research of dissertation seeks a relationship between literature and mysticism in the works of the Bishop Helder Camara. It begins with a realization that mysticisms, though not common, in its attitude, in an effort to form a union between reality and transcendence, necessitating a corresponding courageous attitude to accept a "state non-being" which represents a way and proportions a listing and reception of the divine, integrating faith and life, caking its practitioners an experience of God. The mystics can creatively use literary language. When they narrate histories, describe projects, write discourses, record nature. Meditations or let imaginations flow in configurations which point to dimensions non-experimental to comprehensions which still minimally do not comprehend to his according